Digital Image Correlation. Issue 5 (May 2015) - Wilson, Anthony J.; Chin, Bianca C.; Hsu, Vivian M.; Mirzabeigi, Michael N.; Percec, Ivona
<x xml:space="preserve">Abstract</x> Background: Quantification of facial dynamic motion is paramount for improving cosmetic and reconstructive surgical outcomes. The authors introduce digital image correlation using speckle tracking photogrammetry and Aramis software (GOM mbH, Braunschweig, Germany) to study facial dynamics and demonstrate its application in quantifying botulinum toxin efficacy. Methods: Fourteen subjects were evaluated using a dual camera system and three-dimensional optical analysis. Using Aramis software, the anatomic regions of the glabella, forehead, and total face were identified and highlighted. Tissue strain, defined as either compression or stretch, was measured within these regions over 36 frames during brow furrowing. Each patient was measured before and 2 weeks after injection of 20 units of onabotulinumtoxinA in the glabella. Average stretch and compression in treated areas were analyzed across all available frames. Results were compared using a Wilcoxon signed rank test. Results: After neurotoxin injection, average vertical stretch of the glabella during brow furrowing decreased from 2.51 percent to 1.15 percent (p < 0.05), and average vertical stretch in the forehead decreased from 6.73 percent to 1.67 percent (p < 0.05). Horizontal compression in the glabella decreased from 9.11 percent to 2.60 percent (p < 0.05) and from 4.83 percent to 0.83 percent (p < 0.05) in the forehead. Total facial major strain decreased from 4.41 percent to 3.05 percent (p < 0.05), and total facial minor strain decreased from 5.01 percent to 3.51 percent (p < 0.05). Conclusions: The authors introduce digital image correlation as a novel technology for measuring dynamic rhytid and neurotoxin efficacy. This technique allows for advancements in the study of dynamic aging and neuromuscular disorders. CLINICAL QUESTION/LEVEL OF EVIDENCE: Diagnostic, II.